12th Grader’s Perception Regarding Tertiary Students Teaching Practices - Putu Wahyu Sudewi; Adi Isma; Reski Reski (ELS Journal on Interdisciplinary Studies in Humanities, 2024)
This research investigates students' perceptions of the teaching skills of teaching assistant (TA) tertiary students from the English Education Study Program at the University of Sulawesi Barat, conducted at SMA Negeri 1 Majene. The study aims to assess how well these TA tertiary students perform in key teaching areas, including lesson opening and closing, explaining, questioning, providing reinforcement, introducing variety, guiding small group discussions, and classroom management. Using a qualitative approach, data were collected via questionnaires based on a Likert scale, complemented by guided interviews for qualitative insights. The findings reveal that TA tertiary students received high ratings in explaining (92%), questioning (84%), and classroom management (85%), with an overall average rating of 81.37%, categorized as "very good". While students appreciated the enthusiasm and clarity TA tertiary students brought to lessons, they identified areas for improvement, such as maintaining classroom order, enhancing reinforcement techniques, and diversifying teaching methods. The study underscores the importance of targeted support and continuous development for TA tertiary students to enhance their teaching efficacy and better meet students' diverse needs.